2014
DOI: 10.1007/s00431-014-2400-9
|View full text |Cite
|
Sign up to set email alerts
|

Tetanus and diphtheria immunity among term and preterm infant-mother pairs in Turkey, a country where maternal and neonatal tetanus have recently been eliminated

Abstract: Vaccinating pregnant women with at least one dose of Td would confer protection for both the term and preterm infant-mother pairs. Therefore, health personnel caring for pregnant women have the responsibility to emphasize the importance of Td vaccination to avoid missed immunization opportunities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In this study, sero-protection in the pregnant women before vaccination was higher than that reported in other studies whose pregnant women also received the DTwP vaccine during childhood. A study conducted in Turkey, with 91 mother-umbilical cord pairs, detected 50% sero-protection against diphtheria and 58.0% against tetanus in pregnant women not vaccinated with Td [ 23 ]. A study in China, with 194 mother and umbilical cord pairs, showed 44.3% sero-protection of pregnant women against diphtheria, using a sero-protection cut-off point of ≥0.1, while the sero-protection against tetanus was 52.6% (0.01–0.1) and 28.1% (>0.1–1.0) [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, sero-protection in the pregnant women before vaccination was higher than that reported in other studies whose pregnant women also received the DTwP vaccine during childhood. A study conducted in Turkey, with 91 mother-umbilical cord pairs, detected 50% sero-protection against diphtheria and 58.0% against tetanus in pregnant women not vaccinated with Td [ 23 ]. A study in China, with 194 mother and umbilical cord pairs, showed 44.3% sero-protection of pregnant women against diphtheria, using a sero-protection cut-off point of ≥0.1, while the sero-protection against tetanus was 52.6% (0.01–0.1) and 28.1% (>0.1–1.0) [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, only small amounts of maternal IgG are transferred in the first trimester, with an estimated transplacental transfer of approximately 10% of maternal IgG concentrations by 17–22 weeks gestation (25). The concentration of maternal IgG in infant cord blood reach approximately 50% of the maternal IgG levels by 30 weeks gestation (25) and by 37–40 weeks of gestation, infant cord blood concentrations of maternal IgG often exceed that of maternal serum by the delivery time point in full term, healthy pregnancies (2528). Thus, while maternal IgG is transferred across the placenta throughout pregnancy, the majority of the transfer occurs in the last trimester of gestation; possibly due to an increase in the surface area of IgG uptake from maternal blood with higher gestational age.…”
Section: Mechanisms Of Igg Transplacental Transfermentioning
confidence: 99%
“…Importantly, IgG subclass responses are distinctly modulated against different antigens (36). For example, the IgG response against polysaccharide antigens such bacterial capsule of Group B streptococcus or Haemophilus influenzae Type B (HiB) is primarily IgG2 subclass whereas the response against tetanus toxoid is predominantly IgG1 (28, 36). In addition to IgG subclass, antibody avidity (37, 38) and Fc region glycosylation profile may influence transplacental transfer (39, 40).…”
Section: Mechanisms Of Igg Transplacental Transfermentioning
confidence: 99%
“…Maternal protective IgG is transferred from the maternal to the fetal circulatory system via the placenta, and this process begins in the first trimester of pregnancy [ 2 ]. By 37–40 weeks of gestation, maternal passively acquired IgG concentrations in newborns can exceed maternal IgG serum levels in normal pregnancies [ 3 7 ]. Yet, the molecular mechanisms of transplacental transfer of maternal IgG remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%